Implementing patient-public engagement for improved health: Lessons from three Ghanaian community‐based programmes - Samuel E. Ankomah; Adam Fusheini; Sarah Derrett (Wiley, 2023)
Abstract Background Community‐based health interventions have been implemented as a key strategy for achieving improved health outcomes in Ghana. Effectiveness, however, largely depends on the successful implementation of patient-public engagement (PPE). Although several PPE studies have been conducted in Ghana, little research has been done to understand the specific role of PPE in the context of implementing community‐based health programmes. This paper, therefore, examines the extent of PPE implementation in three selected community‐based health programmes (Community‐based Health Planning and Service [CHPS], Community‐based Maternal and Child Health and Buruli Ulcer) to understand their specific effects on health outcomes. Methods Three focus groups, involving 26 participants, were held in three districts of the Ashanti region of Ghana. Participants were mainly health service users involving community health committee members/volunteers, residents and health professionals. They were invited to participate based on their roles in the design and implementation of the programmes. Participants focused on each of Rifkin's spider‐gram components. Data were transcribed and analysed descriptively using NVIVO 12 Plus. Results PPE implementation was found to be extensive across the three programmes in specific areas such as organisation and resource mobilisation. PPE was more restricted in relation to community needs assessment, leadership and management, particularly for the CHPS and Buruli Ulcer programmes. Conclusion Findings suggest that benefits from community‐based health interventions are likely to be greater if PPE can be widely implemented across all dimensions of the spider‐gram framework.